Intellectual property rights and agricultural technology: interplay and implications for India - Ravishankar, A.; Archak, Sunil (2000)
With the Plant Varieties Protection and Farmers Rights' Bill being referred to a select parliamentary committee, the advent of an IPR regime in the agricultural sector is imminent. This paper attempts to sketch heuristically, the research domain and its portfolio in the agricultural sector. It is argued that inter alia, the legal and policy framework will determine the shape of things to come. Based on the nature of protection for different technologies, the role of probable stakeholders and their plausible impacts are examined. - Reproduced
Keywords: Intellectual property - India; Intellectual property